2017
DOI: 10.1590/1516-4446-2016-2107
|View full text |Cite
|
Sign up to set email alerts
|

Depression and psychodynamic psychotherapy

Abstract: Depression is a complex condition, and its classical biological/psychosocial distinction is fading. Current guidelines are increasingly advocating psychotherapy as a treatment option. Psychodynamic psychotherapy models encompass a heterogeneous group of interventions derived from early psychoanalytic conceptualizations. Growing literature is raising awareness in the scientific community about the importance of these treatment options, as well as their favorable impact on post-treatment outcomes and relapse pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 32 publications
0
20
0
Order By: Relevance
“…Depression is a mood disorder characterized by persistent feeling of sadness, loss of interest, decline in thinking and cognitive function, and disorder of physiological function [1,2]. The WHO reported that it could be the third principal cause of disability worldwide by 2020 [3]. In addition, depression can easily lead to suicide and decreased fertility [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Depression is a mood disorder characterized by persistent feeling of sadness, loss of interest, decline in thinking and cognitive function, and disorder of physiological function [1,2]. The WHO reported that it could be the third principal cause of disability worldwide by 2020 [3]. In addition, depression can easily lead to suicide and decreased fertility [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Depression, characterized by depressed mood, diminished interests, avolition, worthlessness and hopelessness, raises concern in global public health (Otte et al, 2016). The lifetime prevalence of depression is estimated at 2-20%, and more than 60% of depression cases jeopardize the quality of life (Zilcha-Mano et al, 2014;Ribeiro et al, 2018). Depression is a multifactorial and heterogeneous disorder with abundant etiologies, molecular alterations and multiple pathway dysregulations.…”
Section: Introductionmentioning
confidence: 99%
“…The loss of interest and pleasure in daily life and feelings of guilt, uselessness, and self‐punishment, low self‐esteem, loss of confidence, and lack of support may be identified, in addition to suicidal ideas and attempted self‐aggression or suicide. Cognitive changes include lack of concentration and reduced attention, recurrent pessimistic and negative thoughts about the individuals themselves relative to the past and future …”
Section: Introductionmentioning
confidence: 99%
“…Cognitive changes include lack of concentration and reduced attention, recurrent pessimistic and negative thoughts about the individuals themselves relative to the past and future. [1][2][3] It is believed that by 2020, depression will be the second major cause of incapacity. 4 A prevalence of depression of approximately 8% was verified in a population-based study (n = 3,003) conducted in Lethonia.…”
Section: Introductionmentioning
confidence: 99%